Religion and the secular in Eastern Germany, 1945 to the present - Peperkamp, Esther; Rajtar, Małgorzata (Studies in Central European histories, 2010)
Cover13; -- Copyright13; -- Contents -- Acknowledgments -- Notes on Contributors -- Map of eastern Germany -- Introduction -- 1. Science as Religion: The Role of Scientism in the Secularization Process in Eastern Germany -- 2. Secular Rituals and Political Commemorations in Eastern Germany, 1945-1956 -- 3. The Limits of Politicization of the Schools in the SED State: The Catholic Eichsfeld Region and the Protestant Erzgebirge 8211; A Comparison -- 4. Positions and Pathways of Families within the Religious Field of East Germany: Three Catholic Case Studies -- 5. Between Menschlichkeit and Missionsbefehl: God, Work, and World among Christians in Saxony -- 6. Religious Socialization in a Secular Environment: Jehovahs Witnesses in Eastern Germany -- 7. Young Eastern Germans and the Religious and Ideological Heritage of their Parents and Grandparents -- 8. The Rehabilitation of Ex-Offenders in Eastern Germany: A Religious-Secular Configuration -- 9. Church Buildings in Eastern Germany: Houses of God or Tourist Attractions? -- Conclusion: Dealing with Two Masters Commands 8211; Explorations of the Complexities of Religious Life under a Dictatorial Regime -- Index